2008
DOI: 10.1186/1471-2466-8-23
|View full text |Cite
|
Sign up to set email alerts
|

High serum concentrations of autoantibodies to HSP47 in nonspecific interstitial pneumonia compared with idiopathic pulmonary fibrosis

Abstract: Background: The pathological diagnosis of idiopathic interstitial pneumonias (IIP) by surgical lung biopsy is important for clinical decision-making. However, there is a need to use less invasive biomarkers to differentiate nonspecific interstitial pneumonia (NSIP) from other IIP such as usual interstitial pneumonia (UIP). Heat shock protein (HSP) 47, a collagen-specific molecular chaperone, is involved in the processing and/or secretion of procollagen. HSP47 is increased in various fibrotic diseases. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
0
19
1
1
Order By: Relevance
“…In fact, we have shown that anti-Th/To autoantibodies facilitate the differentiation of patients with SSc without scleroderma from those with IPF [28]. Additional antibodies include those directed against HSP47, which are detected at higher levels in the serum of patients with idiopathic NSIP compared with IPF patients [29]. Antivimentin antibodies were also detected in sera of patients with IPF and NSIP [30].…”
Section: Autoantibodies and Other Serum Biomarkersmentioning
confidence: 87%
“…In fact, we have shown that anti-Th/To autoantibodies facilitate the differentiation of patients with SSc without scleroderma from those with IPF [28]. Additional antibodies include those directed against HSP47, which are detected at higher levels in the serum of patients with idiopathic NSIP compared with IPF patients [29]. Antivimentin antibodies were also detected in sera of patients with IPF and NSIP [30].…”
Section: Autoantibodies and Other Serum Biomarkersmentioning
confidence: 87%
“…Only very limited release was noted from cultured fibroblasts. Recently, highserum auto-antibodies to HSP47 or HSP47 itself have been reported under inflammatory conditions, such as interstitial pneumonia and mixed connective tissue disease (Yokota et al, 2003;Kakugawa et al, 2008). If HSP47 is released from cancers in patients with UC, its detection in serum would be helpful for the clinical detection of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…More direct evidence is derived from reports of autoantibody and T cell responses to a variety of ubiquitously expressed proteins in patients with ILD (810). However, these putative antigens are not tissue specific and so it is not clear how they could cause a disease process limited to the lung.…”
Section: Introductionmentioning
confidence: 99%